Hydrogen gas: a potential novel tool to enhance abiotic stress tolerance in plant - Yayu Liu; Lijuan Wei; Li Feng; Jianzhong Tie; Weibiao Liao (Plant Stress)
Hydrogen gas (H2) is a unique gaseous molecular messenger, and it influences several physiological processes in plants. In the review, we cover current developments in the study of the role of H2 in plant response to abiotic stresses. Overall, H2 can enhance environmental stress tolerance by strengthening antioxidant defense mechanisms, increasing photosynthetic capacity, re-establishing ion homeostasis, preserving nutritional homeostasis, and regulating flavonoid pathways. In addition, we discuss the interactions of H2 with other signaling molecules in enhancing plant abiotic stress tolerance. Furthermore, this review is focused on discussing the potential mechanisms of H2 action in plants under adversity stress. Nevertheless, there is little evidence regarding the molecular mechanisms mediated by H2 under abiotic stress. More studies are required to advance our understanding of the potential applications of H2 in response to abiotic stresses in plants.